ANALISIS TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT KEPABEAN - Toton Hartanto (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2015)
The objective of this study is to examine the effect of auditee selection, auditor competence and independence on the customs audit quality. It is conducted at the Directorate General of Customs and Excise with Customs audit data in 2013 and 2014. It is a quantitative study using generalized least squares estimation methods on structural equation modeling with IBM SPSS AMOS version 22. The result of this study shows that auditor independence has a positive effects on customs audit quality, but it need improvement on the mechanism of cintigent performance reward, otherwise, the auditee selection has no effect on customs audit quality therefore it is important to develop a better predictive audit yield. Moreover, auditor competence also has ni effect on customs audit quality, it has to take a necessary action against the sympstons of fatigue.